Approaches and adjuncts used by physiotherapists when suctioning adult patients who are intubated and ventilated in intensive care units in Australia and New Zealand: A cross-sectional survey - Tan, Charissa; Harrold, Megan; Hill, Kylie (Elsevier Inc, 2016)
Background: Suctioning is an integral component of care for patients who are intubated and ventilated in an intensive care unit (ICU). There appears to be no published data of physiotherapy suctioning practices in Australia or New Zealand. Objective: To describe suctioning practices and the factors which have shaped these practices, of experienced physiotherapists working with adults who are intubated and ventilated in an ICU across Australia and New Zealand. Areas of investigation focused on: (i) suctioning approach (i.e. open vs. closed system); (ii) use of adjuncts to suctioning such as hyperoxygenation, hyperinflation and saline lavage; (iii) use of subglottic suctioning and; (iv) factors influencing suctioning practices. Methods: Electronic surveys were emailed to experienced physiotherapists working in ICUs across Australia and New Zealand which had the capacity to intubate and ventilate adult patients for =24. h. Results: The participation rate was 84.8% (112/132). Closed suction system was used in most ICUs (97/112, 86.6%). Hyperoxygenation was commonly performed on 'all' or 'most' patients before suctioning (71/112, 63.4%), but less frequently after suctioning (38/112, 33.9%). Hyperinflation was infrequently performed on 'all' or 'most' patients before (22/112, 19.6%) or after suctioning (22/112, 19.6%). Saline lavage and subglottic suctioning were infrequently performed on 'all' or 'most' patients (3/112, 2.7%; 17/112, 15.2%, respectively). 'Personal experience' and 'established practice in the ICU' had the greatest influence on suctioning practices. Conclusions: Most ICUs in Australia and New Zealand are equipped for closed system suctioning. As hyperoxygenation minimises desaturation during suctioning, there may be scope for a larger proportion of physiotherapists to use this adjunct. The practice of hyperinflation before and after suctioning was uncommon despite the emerging evidence for improved lung compliance with this procedure. Subglottic suctioning was infrequently available as a choice for physiotherapists despite the strong evidence, which suggests an evidence-practice gap. © 2017 Australian College of Critical Care Nurses Ltd.